2004
DOI: 10.1194/jlr.m400144-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Preferential inhibition of paraoxonase activity of human paraoxonase 1 by negatively charged lipids

Abstract: To determine the causes responsible for a preferential decrease of paraoxonase activity, which has been observed in the serum of patients with cardiovascular diseases, the inactivation or inhibition of paraoxonase 1 (PON1) by various endogenous factors was examined using paraoxon or phenyl acetate as a substrate. When purified PON1 was incubated with various endogenous oxidants or aldehydes, they failed to cause a preferential reduction of paraoxonase activity, suggesting no participation of the inactivation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
1
19
2
Order By: Relevance
“…In contrast, an in-vitro study by Nguyen and Sok [65 ] showed that lysophosphatidylglycerol and lysophosphatidylinositol inhibited PON1 activity, whereas lysophosphatidylserine or lysophosphatidylcholine had no such effect, suggesting that endogenous lipids can affect PON1 activity, and their effect depends on the type of their head group. Finally, cholesterol supplementation in rats resulted in a significant decrease in hepatic PON1 synthesis, whereas it had no effect on other hepatic antioxidant enzyme activities [66].…”
Section: Figure 2 the Effect Of Statins And Polyphenols On Paraoxonasesmentioning
confidence: 79%
“…In contrast, an in-vitro study by Nguyen and Sok [65 ] showed that lysophosphatidylglycerol and lysophosphatidylinositol inhibited PON1 activity, whereas lysophosphatidylserine or lysophosphatidylcholine had no such effect, suggesting that endogenous lipids can affect PON1 activity, and their effect depends on the type of their head group. Finally, cholesterol supplementation in rats resulted in a significant decrease in hepatic PON1 synthesis, whereas it had no effect on other hepatic antioxidant enzyme activities [66].…”
Section: Figure 2 the Effect Of Statins And Polyphenols On Paraoxonasesmentioning
confidence: 79%
“…In vitro studies have shown that oleic acid protects PON1 from oxidative inactivation, while polyenoic fatty acids inhibited PON1 activity [88]. However, oleic acid itself has also been shown to inhibit PON1 activity, possibly binding to a different site [89]. …”
Section: Factors That May Increase Pon1 Activity or Expressionmentioning
confidence: 99%
“…Negatively charged lipids, including saturated, monounsaturated, and polyunsaturated DFAs, have all been reported to inhibit PON1 enzyme activity in vitro [23], with polyunsaturated fatty acids having the largest inhibitory effect [24]. However, monounsaturated fatty acids (and to a lesser extent, saturated fats) have also been shown to protect PON1 from ascorbate/copper-mediated oxidative inactivation [24,25].…”
Section: Introductionmentioning
confidence: 99%